Une revue d’études germaniques à vocation interdisciplinaire et interculturelle - Christine Maillard (Recherches Germaniques)
The contribution offers an overview of the history of the journal Recherches germaniques from its inception in 1971 and shows how the journal’s focus on cultural history and literary studies of German-speaking countries has evolved in the city of Strasbourg, Franco-German and international contexts